Mechanical properties of ultra-high performance concrete containing silica fume /Suriafazlin Ismail - Suriafazlin, Ismail (2012)
This thesis presents an investigation to produce ultra-high performance concrete (UHPC) incorporating silica fume with or without steel fibers. The study was carried out to develop UHPC mixes to achieve the targeted strength of 120 MPa at the age of 28 days. The early stage of this study is to determine appropriate materials and cement content to achieve not only the targeted strength of 120 MPa but as well the workability of concrete of 150-300 mm slump flow. Several factors such as method of curing, selected materials and production cost were put into consideration during the investigations in order to develop economical and green concrete. Various UHPCs were produced using Sherbrooke design method with some modification since no coarse aggregates were used. UHPC mixtures were designed with fixed water-binder (W/B) ratio of 0.22, two series of cement content i.e. 875 and 900 kg/m3 and silica fume content in the range of 0 to 30% of cement by weight. Other materials used to produce UHPC of 120 MPa were silica sand with two sizes i.e. 70% of 600μm size and 30% of 0.6-2.0 mm size and superplasticizer of 2% of binder content. The fresh UHPCs were tested for workability with respect to slump flow. Test results for fresh properties showed that the slump flow increased with higher amount of total binder. The hardened UHPCs were tested for compressive strength, flexural strength, splitting tensile strength, ultrasonic pulse velocity, static modulus of elasticity, surface hardness, the rebound number and initial surface absorption test. In general, UHPC indicated good durability. From the studies carried out, it can be concluded that UHPC can be produced by incorporating silica fume and suitable to be used in precast industry, thus supporting the Governments initiatives in promoting industrialized building systems (IBS) usage in the local construction industry.